Updating predictors of endoscopic recurrence after ileocolic resection for Crohn disease - Sara Monteiro,; Tiago Cúrdia Gonçalves,; Pedro Boal Carvalho,; Maria João Moreira,; José Cotter, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Identifying predictors of endoscopic recurrence (ER) has become very important to guide the decision of postoperative strategy. This study aimed to determine the rate of endoscopic recurrence until 12 months after ileocolic resection for Crohn disease (CD) in a cohort and identify its possible predictors. Materials and Methods: We conducted a retrospective single-center study that included patients with CD who underwent ileocolic resection between 2003 and 2014. ER was defined according to the Rutgeerts’ score, defined as i2, i3, or i4 at ileocolonoscopy that was performed 6-12 months after surgery. The patients were classified into two groups according to the Rutgeerts´ score: non-ER (Rutgeerts i0/i1) and ER (Rutgeerts ≥i2). Multivariate logistic regression analysis was performed, including significant variables on univariable analysis, to identify ER predictors. Results: Forty-two patients were included. The mean period of the first postoperative colonoscopy was 9 months, and ER was observed in 25 patients (59.5%). The perianal disease and shorter duration of CD were the only ER predictors (p=0.024; OR, 8.36; 95% CI, 1.329-52.642 and p=0.039; OR, 0.965; 95% CI, 0.933-0.998, respectively). Conclusion: Endoscopic recurrence affects almost two-thirds of patients with CD after ileocolic resection, with perianal involvement and a shorter duration of disease being significant risk factors. These factors may indicate a more aggressive disease associated with rapid progression and support the need of intensive early treatment to improve patients’ outcomes. Cite this article as: Monteiro S, Gonçalves TC, Carvalho PB, Moreira MJ, Cotter J. Updating predictors of endoscopic recurrence after ileocolic resection for Crohn disease. Turk J Gastroenterol 2017; 28: 260-5.